Integrated Soil Health Management for Plant Health and One Health: Lessons From Histories of Soil-borne Disease Management in California Strawberries and Arthropod Pest Management - Muramoto, Joji; Parr, Damian Michael; Perez, Jan; Wong, Darryl G. (Frontiers in Sustainable Food Systems, 2022)
Many soil health assessment methods are being developed. However, they often lack assessment of soil-borne diseases. To better address management strategies for soil-borne disease and overall soil and plant health, the concept of Integrated Soil Health Management (ISHM) is explored. Applying the concept of Integrated Pest Management and an agroecological transdisciplinary approach, ISHM offers a framework under which a structure for developing and implementing biointensive soil health management strategies for a particular agroecosystem is defined. As a case study, a history of soil-borne disease management in California strawberries is reviewed and contrasted with a history of arthropod pest management to illustrate challenges associated with soil-borne disease management and the future directions of soil health research and soil-borne disease management. ISHM system consists of comprehensive soil health diagnostics, farmers’ location-specific knowledge and adaptability, a suite of soil health management practices, and decision support tools. As we better understand plant-soil-microorganism interactions, including the mechanisms of soil suppressiveness, a range of diagnostic methodologies and indicators and their action thresholds may be developed. These knowledge-intensive and location-specific management systems require transdisciplinary approaches and social learning to be co-developed with stakeholders. The ISHM framework supports research into the broader implications of soil health such as the “One health” concept, which connects soil health to the health of plants, animals, humans, and ecosystems and research on microbiome and nutrient cycling that may better explain these interdependencies.